DAMPAK KOMPENSASI FINANSIAL DAN NON-FINANSIAL TERHADAP KINERJA KARYAWAN INDUSTRI JASA KEUANGAN - Eka Putra (Sekolah Tinggi Ilmu Ekonomi Riau, 2026)
Abstract : The purpose of this research is to determine the effect of compensation on employee performance at PT. Adira Dhinamika Multi Finance Branch 2 Pekanbaru. To achieve this aim, research was conducted using a sample of 46 people, using the census method. The data analysis method uses simple linear regression. Based on the partial t test results, it was found that compensation had a significant effect on employee performance at PT. Adira Dhinamika Multi Finance Branch 2 Pekanbaru, this was proven based on the t test, it was found that the t-count was greater than the t-table (2,887 > 2,015). The magnitude of the influence of the compensation variable on the employee performance variable is 0.359 (35.9%), this is proven based on the results of the determination test where an R2 value of 0.359 is obtained. It is hoped that the recommendations that can be put forward are for the company to provide allowances for positions because this received the lowest response from respondents.